PERTENTANGAN KELAS SOSIAL PADA TOKOH UTAMA DALAM DRAMA THE HEIRS BERDASARKAN PERSPEKTIF TEORI SASTRA MARXIS - Basid, Abdul; Zulhizawati, Zulhizawati; Hamzah, Muh. Zuhdy (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purpose of this study is to reveal the form and cause of social class opposition to the main character in drama the heirs based on the perspective of Marxist literary theory. The type of this research is descriptive qualitative research. The main data source in this study is the drama The Heirs. The technique of data collection is watching, reading, and record. While the technique of data analysis is Miles and Huberman model. The results of this study is: 1) the form of social class disagreement on the main character in the drama The Heirs is oppression; and 2) the cause of social class opposition to the main character in the drama The Heirs is: a) the relationship between the bourgeoisie and the proletarian class; and b) the implementation of hierarchical system in Jeguk High School.